The urban ecological transition and the future of Europe’s nightlife industry - Nofre, J.; Garcia-Ruiz, M. (World Leisure Journal, 2023)
The current climate emergency and the emergence of a stagflation scenario in Europe have revealed the scarce presence of environmental and resilience-related goals not only in the economic and financial viability plans of the nightlife industry but also in the different tools of nightlife governance already introduced in some European cities. In fact, the recovery and resilience plans of more than a third of the countries of the European Union, which constitute the central mechanism for the ongoing ecological urban transition, do not mention the nightlife industry nor the creative night culture, whose importance is vital for many urban festivals. Despite that, some nightlife entrepreneurs have begun to adapt their businesses to the current urban ecological transition in Europe. Meanwhile, a large part of the scientific community does not seem to be interested in the economic and environmental challenges affecting Europe’s nightlife industry. For the authors of this article, if nightlife is revealed to be central to the socio-emotional wellbeing of many people in our (post-)pandemic world, the “greening” of the nightlife industry should arise as a central topic in the short and medium-term for academics researching in the fields of tourism, hospitality, leisure, and urban studies.